Case study: Thyrotoxicosis on women with complete hydatidiform molar pregnancy - Gagah Baskara Adi Nugraha; Pugud Samodro (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Thyrotoxicosis defined as a clinical manifestation of excess circulating thyroid hormone. Epidemiologic investigation reports 0.2% of thyrotoxicosis is caused by hydatidiform mole. The New England Trophoblastic Disease Centre (NETDC) mentioned that 20% of hydatidiform mole cases have thyrotoxicosis as one of its complications. The basic pathogenesis of thyrotoxicosis is the similarity of the HCG subunit to TSH which results in excessive stimulation of thyroid hormone. We present thethyrotoxicosis case in a 15-weeks pregnant woman with complete hydatidiform mole. The patient admitted to the hospital with blackish-red coloured bleeding and several hyperthyroidism complaints, laboratory test showed elevated levels of HCG and thyroid hormone and decreased TSH. Imaging studies done with ultrasound showed with snowflake pattern. The patient then treated with thyroid hormone suppressant therapy before the hydatidiform mole evacuation. Normalization of thyroid hormone levels should be made immediately before the mole evacuation to avoid life-threatening thyroid storm complications.